ANALYSIS OF THE INFLUENCE OF KAIZEN CULTURE AND WORK ETHOS ON THE PERFORMANCE OF EMPLOYEES IN DISCIPLINE MEDIATION AT THE REGIONAL OFFICE OF THE MINISTRY OF RELIGION IN SOUTH SULAWESI PRO - Mahlia Muis; Rahmania; Haeriah (Journal of Entrepreneurship and Financial Technology, 2023)
This study plans to research the impact of kaizen culture and hard working attitude on representative execution through disciplinary variables in the workplace. The kaizen culture is a methodology that empowers constant improvement inside the association, while the hard working attitude mirrors the qualities, mentalities and responsibility of representatives towards their work. Discipline is the capacity of workers to reliably keep hierarchical guidelines and methodology. This study utilizes a quantitative methodology with an overview strategy, where information is gathered from representatives at different levels and offices inside the association. The examination instrument was a poll that deliberate the degree of kaizen culture, hard working attitude, discipline, and worker execution. The consequences of the information examination showed that there was a positive connection between's kaizen culture and hard working attitude and worker execution. The more grounded the kaizen culture and hard working attitude in the association, the higher the degree of worker execution. Moreover, it was found that discipline goes about as an interceding variable in the connection between kaizen culture and hard working attitude and representative execution. That is, the kaizen culture influences worker execution through the discipline shown by representatives in completing their obligations and obligations.